Intramucosal Early Gastric Cancer With Krukenberg Tumor : A Case Report - Çelebi, Selman; Karaoğlu, Aziz; Çelik, Hüsnü; Elkıran, Emin Tamer; Yazıcı, Serdar; Özgen, Metin; Özercan, İbrahim Hanifi (Fırat University, 2005)
Krukenberg tumor is classically defined as metastatic ovarian neoplasms from the gastrointestinal tract. The primary tumor is frequently from stomach but may also be from colon or biliary tract. Intramucosal early gastric cancer with Krukenberg tumor have been very rarely reported. We herein present a case of Krukenberg tumor that derivated intramucosal early gastric cancer. Endoscopic examination of the stomach should be carefully done at the Krukenberg cases. In addition there should be removed a lot of endoscopic biopsies ©2005, Fırat University, Medical School

Krukenberg tümörleri, klasik olarak gastrointestinal kanaldan kaynaklanan metastatik over neoplazmları olarak tanımlanır. Primer tümör sıklıkla midededir ama kolon ve biliyer kanaldan da kaynaklanabilir. İntramukozal erken mide kanserinden kaynaklanan Krukenberg tümörleri oldukça nadir bildirilmiştir. Biz burada intramukozal erken mide kanserinden kaynaklanan bir Krukenberg olgusunu sunuyoruz. Krukenberg tümörlü olgularda endoskopik inceleme dikkatle yapılmalı ve çok sayıda endoskopik biyopsiler alınmalıdır. ©2005, Fırat Üniversitesi, Tıp Fakültesi
İntramukozal Erken Mide Kanseri ile Birlikte Krukenberg Tümör: Olgu Sunumu